Biogenic selenium nanoparticles in biomedical sciences: properties, current trends, novel opportunities and emerging challenges in theranostic nanomedicine of selenium - Zambonino Soria, Marjorie Cristhine (2021)
In recent years, nanotechnology has revolutionized healthcare strategies by providing remarkable advances in the diagnosis, treatment and prevention of diseases. Owing to their unique properties including enhanced bioavailability, improved targeting, and significantly reduced toxicity, nanoparticles have gained tremendous research interest in the current biomedical sector. Selenium (Se) is an important dietary supplement and an essential trace element incorporated in selenoproteins with growth‐modulating properties and cytotoxic mechanisms. Although it plays a vital role in many biological and physiological processes, Se usually possesses a narrow therapeutic window with a low degree of absorption and delicate safety margins. Therefore, selenium nanoparticles (SeNPs) have been broadly used as a novel therapeutic and diagnostic platform with decreased toxicity and exceptional benefits against oxidative stress and inflammation-mediated disorders. In the need of developing eco-friendly, inexpensive, simple and high-throughtput biomedical agents that can also ally theranostic purposes and present negligible side effects, biogenic SeNPs have received special attention. Since previous studies have failed to evaluate the potential biomedical applications of biogenic SeNPs in both therapeutics and diagnostics fields, the present review discusses in detail the role of biosynthesized SeNP as an innovative theranostic agent for personalized nanomedicine-based treatments. In addition, it highlights the unique biological, physico-chemical, optoelectronic and catalytic properties of Se nanomaterials. Furthermore, it addresses the significance of nanosizing on pharmacological activity (pharmacokinetics and pharmacodynamics) and cellular interaction of SeNPs. Finally, this review explores the role of SeNPS in the ongoing scenario of pandemic (SARS-CoV-2) and presents key future prospects in translational nanomedicine.